Legal protection of minors who marry without an application for dispensation of marriage - Marlin, Marlin; Sariah, Siti (Institute Of computer Science (IOCS), 2025)
This study aims to determine the form of Legal Protection for Minors Who Marry Without a Marriage Dispensation Application in Latoma District, Konawe Regency. This study uses a cumulative research method using an empirical juridical approach. The primary sources in this study are married minors, judges of religious courts and communities. In data collection, field observation, interviews and documentation methods are used. The results show that for underage marriages that take place without a marriage dispensation, it will result in the absence of a guarantee of legal protection from a competent institution that can provide a guarantee that the marriage that occurs is not a violation of the rights of children and in contrast to a minor marriage that receives a determination of marriage dispensation, the role of the court is significant in providing a guarantee of protection for children. Marriage dispensation is necessary in terms of fulfilling the order of Law Number 16 of 2019 concerning Marriage, that deviations from the age of marriage in the Marriage Law can be requested for dispensation to the Religious Court or other officials appointed by both parents from the male and female sides.